Engineering optimisation of commercial facemask formulations capable of improving skin moisturisation. (3rd October 2019) - Mehta, P.; Picken, H.; White, C.; Howarth, K.; Langridge, K.; Nazari, K.; Taylor, P.; Qutachi, O.; Chang, M.‐w.; Ahmad, Z.
Abstract: Introduction: The stratum corneum is the biggest obstacle in cosmetics with respect to skin moisturisation. Many approaches have been taken to overcome the barrier, one of which is incorporating natural cosmeceuticals into cosmetic products to enhance moisturisation effects. Here, a commercial facemask formulation was electrospun to develop dry facemasks capable of hosting cosmeceuticals within the pores of incorporated mesoporous silica. Methods: Ethanolic solutions containing 40% w/w of the marketed facemask (7th Heaven Dead Sea peel‐off facemask) and mesoporous silica were prepared and electrically processed at 30 μL min −1 at an applied voltage of 12 ± 2 kV. In vitro characterisation and release studies using fluorescein dye as a model probe were carried out. Results: SEM images confirmed the fibrous nature of the resulting matrix; showing an average fiber diameter of 298.32 nm. The electrospun mask was found to be advantageous due to this fibrous nature providing high active loading capacity whilst demonstrating 100% probe release within 60 min. Contact Angle hysteresis, thermal analysis and Fourier Transform Infrared Spectroscopy (FTIR) presented evidence of compatibility and stability of and within the formulation. Conclusion: Adapting the formulation of a commercial polymeric facemask into an electrospun facemask has shown the versatility of the electrospinning process; now successfully crossing over into the cosmetic industry. Résumé: Introduction: La couche cornée est le premier obstacle à l'hydratation de la peau par des produits cosmétiques. De nombreuses approches ont été adoptées pour surmonter cette entrave, dont l'une consiste à intégrer des cosméceutiques naturels dans les produits cosmétiques afin d'augmenter leur pouvoir hydratant. Ici, la formulation commercialisée d'un masque pour le visage a été modifiée par électrofilage de manière à développer des masques secs pouvant intégrer des cosméceutiques dans les pores de silice mésoporeuse présent dans le produit. Méthodes: Des solutions éthanoliques, contenant 40 % p/p du masque pour le visage commercialisé (masque peel‐off 7th Heaven Dead Sea) et de la silice mésoporeuse ont été préparées et traitées électriquement à 30  μ l/min _ 1, avec une tension appliquée de 12 ± 2 kV. Des études de caractérisation et de libération in vitro ont été menées, utilisant un colorant fluorescéine en tant que sonde. Résultats: Des images SEM ont confirmé la nature fibreuse de la matrice résultante, avec un diamètre de fibre moyen s'élevant à 298, 32 nm. Le masque électrofilé a été jugé avantageux en raison de sa nature fibreuse, qui permet une capacité de charge élevée, ainsi qu'une libération de 100 % de la sonde dans les 60 min. L'hystérèse de l'angle de contact, l'analyse thermique et la spectroscopie infrarouge à transformée de Fourier (IRTF) ont permis d'identifier des preuves de compatibilité et de stabilité dans cette formulation. Conclusion: La possibilité d'adapter la formulation d'un masque pour le visage polymérique déjà commercialisé pour en faire un masque électrofilé montre la polyvalence du processus d'électrofilage, qui fait une apparition remarquable dans le domaine des cosmétiques.